A new rhodopsin R135W mutation induces endoplasmic reticulum stress and apoptosis in retinal pigment epithelial cells. Issue 8 (12th January 2019) - Yu, Yixin; Xia, Xiaobo; Li, Haibo; Zhang, Yangzhou; Zhou, Xiaoyun; Jiang, Haibo
Abstract: Rhodopsin mutations are associated with the autosomal‐dominant form of retinitis pigmentosa (RP). Here we report simultaneous occurrence of RP associated with bilateral nanophthalmos and acute angle‐closure glaucoma in patient with a new mutation in rhodopsin (R135W). ARPE‐19 cells were transfected with myc‐tagged wild‐type (WT) and R135W rhodopsin constructs. The half‐life of WT and R135W rhodopsin was analyzed via cycloheximide chase analysis. We found that R135W rhodopsin was accumulated in the endoplasmic reticulum (ER) and induced unfolded protein response (UPR) and apoptosis. Moreover, chaperone HSP70 alleviated ER stress and prevented apoptosis induced by R135W rhodopsin by attenuating UPR signaling. These findings reveal the novel pathogenic mechanism of RP and suggest that chaperone HSP70 has potential therapeutic significance for RP. Abstract : Endoplasmic reticulum (ER) stress response is involved in retinal degeneration in cells expressing R135W mutant rhodopsin, and HSP70 is able to attenuate ER stress induced by R135W mutant rhodopsin and therefore has potential therapeutic significance for retinitis pigmentosa.